2016
DOI: 10.1016/j.actamat.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of copper/bronze laminates: Role of interfaces

Abstract: a b s t r a c tInterfaces play a crucial role in mechanical behaviors of both laminated and gradient structured materials. In this work, copper/bronze laminates with varying interface spacing were fabricated by accumulative roll bonding and subsequent annealing to systematically study the interface effect on mechanical properties. Heterogeneities exist in chemical composition, grain size, hardness and texture across the interfaces. Simultaneous improvement of strength and ductility with decreasing interface sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
133
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 613 publications
(138 citation statements)
references
References 56 publications
5
133
0
Order By: Relevance
“…In our previous paper [21], such a transient deformation stage has been found to be caused by the back stress hardening due to the deformation incompatibility between different phases over a strain regime corresponding to the elasto-plastic transition stage. Similar behavior in the hardening rate has also been found recently in the other heterogeneous materials, such as gradient structure [57,58], heterogeneous lamella structure [59] and multilayer laminates [60]. During the plastic deformation of this HSSS, load transfer and strain partitioning between two phases will occur since the softer fcc austenite phase are easier to deform than the harder B2 phase.…”
Section: Resultsmentioning
confidence: 54%
“…In our previous paper [21], such a transient deformation stage has been found to be caused by the back stress hardening due to the deformation incompatibility between different phases over a strain regime corresponding to the elasto-plastic transition stage. Similar behavior in the hardening rate has also been found recently in the other heterogeneous materials, such as gradient structure [57,58], heterogeneous lamella structure [59] and multilayer laminates [60]. During the plastic deformation of this HSSS, load transfer and strain partitioning between two phases will occur since the softer fcc austenite phase are easier to deform than the harder B2 phase.…”
Section: Resultsmentioning
confidence: 54%
“…In the past several years, achieving simultaneously high strength and good ductility has been realized by utilizing combinations of length scale, such as multi-layered materials, and bimodal (or multimodal) grain size distributions [1][2][3][4][5][6][7][8][9]. The results of these studies have shown that it is possible in some cases to do better than just a simple trade-off between strength and ductility (i.e.…”
Section: Introductionmentioning
confidence: 80%
“…The results of the last method will be discussed in detail. Different to other reported multi-layered materials, such as copper with bronze [1], Cu-10Zn with Cu [4], and Nb with Cu [5,12,13], single phase IF steel sheets with different initial structures (deformed and annealed) were stacked alternatively into multi-layers in the present experiment. The stacked plates were "welded" together by hot compression, followed by hot/cold deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,7,12,13] Recently, several promising strategies for achieving simultaneous high strength and high ductility have been proposed by tailoring microstructures through heterogeneous and/or hierarchical structures. [2][3][4][5][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Among them, the gradient structure, where the grain size or the substructure size changes gradually along the depth, [5,[20][21][22][23][24][25][26] has great potential in engineering applications due to their superior combinations of strength and ductility. The tensile properties and underlying deformation mechanisms of the gradient-structured metals have been reported recently.…”
Section: Introductionmentioning
confidence: 99%